LXCat: an Open‐Access, Web‐Based Platform for Data Needed for Modeling Low Temperature Plasmas. Issue 1 (1st September 2016) - Pitchford, Leanne C.; Alves, Luis L.; Bartschat, Klaus; Biagi, Stephen F.; Bordage, Marie‐Claude; Bray, Igor; Brion, Chris E.; Brunger, Michael J.; Campbell, Laurence; Chachereau, Alise; Chaudhury, Bhaskar; Christophorou, Loucas G.; et al.
Abstract : LXCat is an open‐access platform (www.lxcat.net ) for curating data needed for modeling the electron and ion components of technological plasmas. The data types presently supported on LXCat are scattering cross sections and swarm/transport parameters, ion‐neutral interaction potentials, and optical oscillator strengths. Twenty‐four databases contributed by different groups around the world can be accessed on LXCat. New contributors are welcome; the database contributors retain ownership and are responsible for the contents and maintenance of the individual databases. This article summarizes the present status of the project. Abstract : LXCat is an open‐access, web‐based platform for storing, exchanging, and manipulating data needed for modeling low‐temperature plasmas. Since its inception in 2009, over 40 people have contributed, by setting up databases or by participating in the development and maintenance of the platform itself, and have helped make LXCat the important resource that it is today in the low‐temperature plasma community.